Connexin 43 upregulation in burns promotes burn conversion through spread of apoptotic death signals. Issue 6 (September 2020) - Feng, Jiajun; Thangaveloo, Moogaambikai; Ong, Yee Siang; Chong, Si Jack; Joethy, Janna-Vale; Becker, David L.
Highlights: Cx43 protein expression in zone of stasis increaases immediately after burn injury and perpetuates more than two-week. Increased cellular apoptosis co-localizes temporally and spatially with the Cx43 expression in the zone of stasis. Cleaved-caspase 3 and Cx43 expression may demarcate the boundary between zone of coagulation and zone of stasis. Cx43 may contribute to the burn conversion through inducing apoptosis of the healthy cells in the zone of stasis after burn injury. Abstract: Background: Burn wounds continue to worsen after initial injury in a process known as burn conversion, which lasts about 3–5 days. It causes burn wounds to enlarge and deepen, leading to greater morbidity. Apoptosis is one of the factors contributing to the conversion of the zone of stasis into the zone of coagulation. Suppression of apoptosis has been associated with reducing burn conversion. Connexin 43 (Cx43) gap junctions facilitate the spread of apoptotic signals from dying cells to healthy neighbouring cells in injured tissues through the bystander effect. Objectives: The study is to understand the role of Cx43 in burn conversion. Methods: In our study, 15 burn tissue samples were arranged into three groups as early (beginning of burn conversion), intermediate (extensive burn conversion) and late (established burn conversion) burns. Results: We found a striking increase in the amount of Cx43 protein expressed in the dermal fibroblasts (identified with heat shock protein 47 (HSP47) staining) in the zone of stasis in early and intermediate burns. These dermal fibroblasts also express high levels of cleaved-Caspase 3 indicating on-going apoptosis. Conclusions: Our findings suggest that elevation of Cx43 may play an active role in burn conversion spreading apoptosis in the early and intermediate burn wound.